GSK-3β Inhibitor CHIR-99021 Promotes Proliferation Through Upregulating β-Catenin in Neonatal Atrial Human Cardiomyocytes. Issue 6 (December 2016) - Wang, Shoubao; Ye, Lincai; Li, Minghui; Liu, Jinfen; Jiang, Chuan; Hong, Haifa; Zhu, Hongbin; Sun, Yanjun
Abstract : Background: The renewal capacity of neonate human cardiomyocytes provides an opportunity to manipulate endogenous cardiogenic mechanisms for supplementing the loss of cardiomyocytes caused by myocardial infarction or other cardiac diseases. GSK-3β inhibitors have been recently shown to promote cardiomyocyte proliferation in rats and mice, thus may be ideal candidates for inducing human cardiomyocyte proliferation. Methods: Human cardiomyocytes were isolated from right atrial specimens obtained during routine surgery for ventricle septal defect and cultured with either GSK-3β inhibitor (CHIR-99021) or β-catenin inhibitor (IWR-1). Immunocytochemistry was performed to visualize 5-ethynyl-2′-deoxyuridine (EdU)–positive or Ki67-positive cardiomyocytes, indicative of proliferative cardiomyocytes. Results: GSK-3β inhibitor significantly increased β-catenin accumulation in cell nucleus, whereas β-catenin inhibitor significantly reduced β-catenin accumulation in cell plasma. In parallel, GSK-3β inhibitor increased EdU-positive and Ki67-positive cardiomyocytes, whereas β-catenin inhibitor decreased EdU-positive and Ki67-positive cardiomyocytes. Conclusions: These results indicate that GSK-3β inhibitor can promote human atrial cardiomyocyte proliferation. Although it remains to be determined whether the observations in atrial myocytes could be directly applicable to ventricular myocytes, the current findings imply that Wnt/β-catenin pathway may be a valuable pathway for manipulating endogenous human heart regeneration.